Prediction of Chatter in CNC Machining based on Dynamic Cutting Force for Ball End Milling - R., Daud; M. M., Noor; K., Kadirgama; M. R. M., Rejab (2009)
This paper presents the suitable depth of cut, spindle speed and feed rate that will be chosen during machining. If thus parameters are not considered, this can provoke abnormal tool behavior such as chatter. Chatter will limit the tool life which only can be use for just a few times. To predict the chatter occurs, the parameters will be use are spindle speed, depth of cut and feed rate. CNC machine will be use. This process will base on dynamic cutting force model for ball end milling. The selections of cutting tool are depends on the process that will done where the chatter can be observed during this machining process. Cold work tool steel (AISI-D2) chosen as a material and its parameter is 100x100x25 mm. Cutter used was high speed steel 2 flute ball nose. Force dynamometer will be use to measure force and 27 tests will be done to observe the chatter occur. Analysis done by referring the result that be measured by force dynamometer. The chatter in ball end milling can be detected from the calculated cutting forces and their frequency spectra. A comparison of the predicted and measured cutting forces demonstrated that the proposed method provides accurate results.